ANALYSIS OF CIRCULATION IN KENTUCKY FRIED CHICKEN RESTAURANT ON PANDANARAN SEMARANG - Widiastuti, Kurnia; Wandira P, Ayu; Nindita, Velma; Wahyudi, M. Agung (International Journal of Sustainable Building, Infrastructure and Environment (IJOSBIE), 2022)
KFC Pandanaran is a fast food restaurant located on Pandanaran Street, Semarang, which has a variety of activities and behavior, including eating, hanging out, doing work, or just drinking coffee. These behaviors require a comfortable dining room as needed. on the integration relationship between space (spatial physical environment) with all activities of individuals/groups of individuals within a certain period. convenient and appropriate spatial planning is one of the advantages of a restaurant. circulation patterns and the characteristics of various restaurant users are things that should be considered to provide user comfort. therefore analysis of circulation patterns with the study of place-centered mapping behavior is needed to determine circulation patterns and user attributes for the convenience of users with a variety of characters. It is intended that the circulation patterns and attributes of restaurant users can be identified at the point of the problem.Keywords: layout, behavior study, attributes